Penggunaan Media Quizizz Dalam Proses Evaluasi Pembelajaran Untuk Meningkatkan Hasil Belajar di Kelas XI IPS 3 SMA Negeri 3 Palembang - Meriyanti Sari; Tyas Masito Mutiara; Kurnisar Kurnisar (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
The problems found in the field based on observations that have been carried out include: students obtain low learning outcomes and students are less active in working on learning evaluations. This study aims to describe the use of the Quizizz application as an interactive quiz medium in the learning evaluation process to improve student learning outcomes in Civics subjects. This research is a Classroom Action Research which consists of planning, implementation, observation, and reflection stages. Data analysis was performed using descriptive analysis (mean and percentage). While the learning completeness criteria are based on individual and classical mastery. The completeness of the learning outcomes obtained in the study were: in the pre-cycle of 46%, in the first cycle of 68%, and in the second cycle of 89%, there was an increase in each cycle. Based on this analysis, it can be said that the use of the Quizizz application can improve the learning outcomes of class XI senior high school students.